Some New Kinds of Continuous Functions Via Fuzzy Neutrosophic Topological Spaces - Fatimah M. Mohammed; Shaymaa F. Motar (Tikrit Journal of Pure Science, 2022)
In this paper, we defined fuzzy neutrosophic continuous